A Thought-Reader's Thoughts Being the Impressions and Confessions of Stuart Cumberland - Cumberland, Stuart C. (Cambridge University Press, 1888)
Although famous throughout Europe for his mind-reading skills, Stuart C. Cumberland (1857–1922) was a staunch critic of the 'rascality' of some spiritualist practices and their practitioners. He claimed that many of the séances and other events which he had experienced were merely fraudulent money-making impostures. He wrote several books on his life as a thought-reader, in which he also revealed the techniques of fake mediums and psychics. (His That Other World, of 1918, is also reissued in this series.) In this 1888 work, Cumberland narrates his own history and career and describes some of his most memorable séances. One of these took place in the House of Commons, where Cumberland subjected none other than the prime minister at the time, W. E. Gladstone, to having his thoughts read. Their encounter made a great impression on the author, who found Gladstone one of his most remarkable subjects
Title from publisher's bibliographic system (viewed on 05 Oct 2015)